ADDITION OF A STATIC MIXER AS A MODIFICATION TO THE CHEMICAL REACTANT FEED PRETREATMENT FOR REDUCING MONOGLYCERIDE CONTENT - Sinaga, Boy; Frandika Darma; Rahmadhani; Saragih, Febri Tuahman; Sofia; Wahyuningtyas, Lala T. (International Journal Multidisciplinary (IJMI), 2026)
Objective: Biodiesel is a sustainable alternative energy that is continuously being developed. Monoglycerides are a contaminant component in biodiesel, causing blockages and abrasiveness in fuel injection. Reducing the monoglyceride component can be achieved using several technologies, one of which is the use of a static mixer to mix methanol (CH3OH) and sodium methoxide (CH3ONa) before being fed into the reactor to optimize the transesterification reaction. Method: This study first simulated the flow velocity profile and turbulence kinetic energy (TKE) in a pipe without a static mixer and a pipe with a static mixer using ANSYS Fluent 2025R1 software. The study consisted of 14 runs, 7 of which were performed without a static mixer and 7 with a static mixer. The production of each run was then analyzed for glyceride components using gas chromatography. Results: The maximum velocity in the pipe without a static mixer is 0.584 m/s and using a static mixer is 1.146 m/s, increasing by 96,2%. The turbulence kinetic energy (TKE) value in the pipe without a static mixer is 0.00235 m2/s2 and using a static mixer is 0.0282 m2/s2, indicating the presence of turbulent flow along the static mixer. The average percentage of monoglyceride components in the treatment without a static mixer is 0.4828% and with a static mixer is 0.4593%. Novelty: This research has never been conducted on a factory scale with a continuous production process so that it will help improve the quality of biodiesel, especially in reducing the monoglyceride component.